2022-RA-591-ESGO Twenty years of experience with less radical fertility-sparing surgery in early-stage cervical cancer: pregnancy outcomes. (20th October 2022) - Robova, Helena; Rob, Lukas; Halaska, Michael; Pichlik, Tomas; Drozenova, Jana; Malikova, Hana
Abstract : Introduction/Background: The standard procedure in cervical cancer is radical hysterectomy (RH) and pelvic lymphadenectomy (PLND). Because of the increasing age of women at childbirth, fertility becomes a major challenge. We present pregnancy results after less radical fertility-sparing surgery in women with IA1, LVSI positive, IA2 and IB1 (<2 cm, infiltration less than half of stromal invasions. Methodology: Laparoscopic sentinel lymph node mapping (SLNM) with frozen section (FS) followed by PLND and 'selective parametrectomy' (removal of afferent lymphatic channels from the paracervix) in case of a negative result was performed in all women. If lymph nodes verified negative by definitive histopathology, patients were treated by simple trachelectomy (IB1) or large cone (IA1/IA2) biopsy 1 week after primary surgery. Results: From 1999 to 2018, 91 women were enrolled in the study (median age 29.1 years, range 21–40). In 76(83.5%) fertility was spared, 13 (17.1%) of them don't want to be pregnant and 63 (82.9%) wished pregnancy. 54 from 63 women conceived (pregnancy rate 85.7%) and 48 from 63 women delivered 58 babies (delivery rate 76.2%). 39 women delivered in term (67.2%), 13 women between 32 and 36+6 weeks of pregnancy, 3 between 28 and 31+6 weeks and 3 between 24 and 27+6 weeks. Only one woman still plan pregnancy. One woman is currently pregnant. Conclusion: Goal of fertility-sparing surgery is not only good oncological results, but also good pregnancy results. Pregnancy results after less radical fertility-sparing procedure seems to be very good (pregnancy rate 82.9% and delivery rate 76.2%). This work is supported by Cooperatio program 207035, Maternal and Childhood Care, 3rd Faculty Medicine, Charles University.